Pengembangan Soal Matematika Untuk Mengukur Kemampuan Pemahaman Konsep Matematis Pada Materi Persamaan Kuadrat - Melsita, Holdia; Erita, Selvia (Malewa: Journal of Multidisciplinary Educational Research, 2023)
In mathematics, there are still many teachers who give less varied tests and are still categorized as low-level understanders. The study aims to acquire the validity of the development of mathematical tests to measure the ability to better understand the concepts of the mathematics about the extent to which students master the formula. With the understanding of the concept the student is able to apply the formula meaningfully and accompanied by reasoning, to link one idea with another idea, and to prove the truth of a formula. The type of research used is Reseach and Development. The data obtained was analyzed with descriptive statistics. This phase of research is called Define, Design, Develop, and Desseminate, or usually called 4-D development. Data collection techniques are done by giving validity sheets of validated subjects before testing to students. The sample in this study was a student of the 11th grade of Tata Busana with a total of 7 students. The results of this study show that the test developed categorized is already very logically valid, whereas empirically based on the validity test there are 1 valid questions and 3 invalid questions, reliability is still categorized low, the difficulty index of questions is not even, and has a poor differential power, so the questions used for this test is good enough.